Clean eats : over 200 delicious recipes to reset your body's natural balance and discover what it means to be truly healthy - Junger, Alejandro. (HarperOne, 2014)
"From Dr. Alejandro Junger, author of the New York Times bestsellers Clean and Clean Gut, comes Clean Eats, a cookbook featuring over 180 delicious, easy-to-prepare, healthy recipes all aimed at helping you restore your natural ability to heal yourself. In Clean, New York City cardiologist Dr. Alejandro Junger provided a life-changing program to aid common ailments resulting from toxins in the standard American diet and chemical-filled environments. Now Dr. Junger's in-demand recipes are available in Clean Eats, a cookbook that takes the program straight to the kitchen and allows readers to start eating Clean today.Beginning with a comprehensive introduction that outlines what Clean eating means, Clean Eats presents over 180 recipes tailored to Clean, Clean Gut, Elimination, and Paleo diets, including detailed nutritional information, a two-week daily menu planner, a weekend detox, and a section on the "Economics of Eating Healthy." Whether you suffer from digestive problems, depression or anxiety, unwanted pounds or simply less-than-stellar health, Dr. Junger provides medically proven ways to manage symptoms without resorting to pills, surgery and other frequently prescribed treatments that merely mask the root of the problem. Clean has already transformed the lives of millions, and with Clean Eats, it's never been easier to jumpstart the journey to a healthier way of life"--